Antibiotic resistant patterns of bacterial isolates from ready-to-eat (RTE) street vended fresh vegetables and fruits in Dhaka City (Bangladesh Journal of Scientific Research, 2012)
Key words: Enteric bacteria; lactose fermenter; non-lactose fermenter; antibiotic resistanceDOI: http://dx.doi.org/10.3329/bjsr.v24i2.10769 Bangladesh J. Sci. Res. 24(2):127-134, 2011 (December)